(IN COMMEMORATION OF THE 115TH ANNIVERSARY OF BIRTH) - V. Yu. Al'bitskii; S. A. Sher; N. P. Drach (Вопросы современной педиатрии)
The article represents the data received during the study of archive documents, scientific works of F.I. Zborovskaya, as well as articles collections of the Institute of Pediatrics of the USSR AMS, pediatric journals and medical newspaper. These materials reflect professional activity and main landmarks in life of F.I. Zborovskaya — one of the most significant researchers at the field of maternity and infancy health care organization in the USSR at 30–40th years of 20th century. Occupying different executive positions, including head of the department of Maternity and Infancy Protection of the USSR National Committee of Health Care (Narcomzdrav), director of the Institute of Maternity and Childhood Protection, which was reformed into the Institute of Pediatrics of the USSR AMS, head of the department of hygiene and children health care organization of the Institute of Pediatrics, and after that — the same post of the Central Institute of the clinical education, F.I. Zborovskaya has always actively participated in scientific and practical activity and carried on huge organization work. Her professional life of a soviet practitioner, scientist and health care organizer is a bright example of devoted service to the protection of mothers and children health.